Gut Microbial Dysbiosis in the Irritable Bowel Syndrome: A Systematic Review and Meta-Analysis of Case-Control Studies - Wang, Lin; Alammar, Nuha; Singh, Rajdeep; Nanavati, Julie; Song, Yiran; Chaudhary, Rahul; Mullin, Gerard E. (Journal of the Academy of Nutrition and Dietetics, 2020)
Irritable bowel syndrome (IBS) is the most common functional digestive condition in the industrialized world. The gut microbiota plays a key role in disease pathogenesis. A systematic review and meta-analysis on case–control studies was conducted to determine whether there is gut microbial dysbiosis in participants with IBS in comparison with healthy controls and, if so, whether the dysbiosis pattern differs among IBS subtypes and geographic regions. This review was conducted and reported according to the MOOSE (Meta-Analysis of Observational Studies in Epidemiology) 2000 and PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) 2009 guidelines. Research articles published up to May 9, 2018 were identified through MEDLINE (PubMed), Cochrane Central Register of Controlled Trials (Cochrane Library), ClinicalTrials.gov, EMBASE, and Web of Science. Study quality was assessed using the Newcastle-Ottawa Scale. Case–control studies of participants with IBS who had undergone quantitative gut microbial stool analysis were included. The primary exposure measure of interest is log10 bacterial counts per gram of stool. Meta-analyses were performed to estimate the mean difference (MD) in gut microbiota between participants with IBS and healthy controls using the random-effects model with inverse variance in Revman 5.3 and R 3.5.1. Publication bias was assessed with funnel plots and Egger’s test. Between-study heterogeneity was analyzed using Higgins I2 statistic with 95% CIs. There were 6,333 unique articles identified; 52 qualified for full-text screening. Of these, 23 studies were included for analysis (n=1,340 participants from North America, Europe, and Asia). Overall, the studies were moderate in quality. Comparing participants with IBS to healthy controls, lower fecal Lactobacillus (MD= –0.57 log10 colony-forming unit [CFU]/g; P<0.01) and Bifidobacterium (MD= –1.04 log10CFU/g; P<0.01), higher Escherichia coli (MD=0.60 log10CFU/g; P<0.01), and marginally higher Enterobacter (MD=0.74 log10CFU/g; P=0.05). No difference was found between participants with IBS and healthy controls in fecal Bacteroides and Enterococcus (P=0.18 and 0.68, respectively). Publication bias was not observed except in Bifidobacterium (P=0.015). Subgroup analyses on participants with diarrhea-predominant and constipation-predominant IBS showed consistent results with the primary results. A subgroup analysis of Chinese studies was consistent with the primary results, except for fecal Bacteroides, which was increased in participants with IBS vs healthy controls (MD=0.29; 95% CI 0.13 to 0.46; P<0.01). Although substantial heterogeneity was detected (I2>75%) in most comparisons, the direction of the effect estimates is relatively consistent across studies. IBS is characterized by gut microbial dysbiosis. Prospective, large-scale studies are needed to delineate how gut microbial profiles can be used to guide targeted therapies in this challenging patient population.